Integrons: A Mobile Genetic Element of Concern in Antimicrobial Resistance Gene Transfer: An Overview - Gidla, Veera Venkata Satyanarayana; V.J, Ajay Kumar; V., Bhanu Rekha; G., Deepan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Abstract Antimicrobial resistance is one of the major global public health problems. There are numerous factors which contribute to the development of antimicrobial resistance. One such factor is integrons which is a mobile genetic element. Integrons contribute to the spread and distribution of antimicrobial resistance genes across diverse bacterial species through horizontal gene transfer. Integrons are made up of three components namely an integrase gene (intI), a primary recombination site (attI) and a promoter region. Integrons transfer resistance genes through transfer of plasmids or through phages. There are two types of integrons such as resistance integrons and super integrons. Resistance integrons are of 4 classes (class I-IV). Class 1 integrons are major contributors of antimicrobial resistance globally and found as contaminant in all ecosystems dominated by humans. The peculiarity of integrons is that they offer a mechanism for quick migration and exchange of various resistance genes. Bacteria with antibiotics, disinfectants and heavy metals discharged into waste streams hotspots are created where intricate interactions and selection events can take place for the interchange of genes and the creation of novel gene combinations.